Moringa oleifera Supplementation Improves Antioxidant Status and Biochemical Indices by Attenuating Early Pregnancy Stress in Beetal Goats - Afzal, Ali; Hussain, Tarique; Hameed, Amjad (Frontiers in Nutrition, 2021)
The study investigated the effects of supplementing different levels of Moringa oleifera leaf powder (MOLP) on antioxidant status and blood biochemical indices during early gestation in Beetal goats. A total of 30 goats were randomly divided into three groups (n=10) comprising control (basal diet without MOLP), 1.6% MOLP group (basal diet + 1.6% MOLP) and 3.2% MOLP group (basal diet + 3.2% MOLP). The experiment started 5 days before estrus synchronization and lasted on day 60 of gestation. The MOLP significantly increased plasma flavonoids in 1.6% as well as 3.2% supplemented group on days 40 and 60 of pregnancy, while total phenolic contents were observed higher in 3.2% supplemented group throughout the experiment in comparison to control group. The supplementation improved plasma total antioxidant capacity (TAC) by decreasing malondialdehyde (MDA) and total oxidant status (TOS) in contrast to the control group. The activities of superoxide dismutase (SOD) and peroxidase (POD) were enhanced in both supplemented groups, whereas catalase (CAT) activity was noticed significantly high in 3.2% supplemented group. The protein contents significantly elevated with 1.6% and 3.2% supplementation levels from day 40 to 60 of the experiment. Plasma sugar level, carotenoids, progesterone profile, and hydrolytic (protease and amylase) enzymes activities were improved only with 3.2% supplementation. The findings suggest that supplementing with 3.2% MOLP provide beneficial effects on early pregnancy stress in Beetal goats.